Costa Rican parents and their beliefs about difficulties in learning math and possible solutions - Meza Cascante, Luis Gerardo (2022)
This study reports the results of an investigation carried out in 2018 with parents of students from 6 public primary education institutions of the Central Canton of Cartago, Costa Rica. The purpose of this research was to identify some beliefs that parents have about mathematics, to inquire about the difficulties they believe their children face when they learn mathematics and about the solutions they envision to overcome them. The research was developed in the qualitative modality, with elements of participatory action research, using projective techniques and cooperative work for data collection.The research reveals that the majority of mothers and fathers conceive mathematics, predominantly, as a complicated, difficult, boring, horrible and scary discipline; as well as a necessary, useful, important, beautiful, fun, interesting, entertaining and easy subject, but in fewer numbers. It was identified that the beliefs about the difficulties faced by their children in learning mathematics environments are due to methodological issues linked to the lectures, an instrumentalist perception of mathematics, inherent problems associated to structural characteristics of the Costa Rican public educational system , large groups of students and the negative effect of some emotional factors associated with the subject. The beliefs about the possible solutions are synthesized in the convenience of increasing the training and education of educators so that they can rethink the educational processes in aspects such as didactic strategies or the classroom climate.